CYBER PSYCHOLOGY IN LEADERSHIP (FOCUS: MAINTAING EMPLOYEE MENTALLY WELL BEING UNDER A CONSTANT PERFORMANCE MONITORING SYSTEM) - Wiwin Widya Wanti; Muhammad Faizal Mufti Ali; Safira Nihayatun Niswa; Mochammad Isa Anshori (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Digital transformation and the escalation of cybersecurity threats have prompted organizations to adopt real-time performance monitoring systems to strengthen control and data protection. While effective in enhancing performance visibility and compliance, constant surveillance has the potential to induce psychological pressure and cognitive fatigue, which impacts employee mental well-being. This study aims to analyze the relationship between cybersecurity monitoring, cognitive fatigue, and mental well-being, as well as to examine the role of leadership in maintaining a balance between organizational control needs and the psychological health of employees. The research employs a qualitative approach with an integrative literature review strategy that synthesizes empirical and conceptual findings from various recent scientific studies. Analysis was conducted through thematic analysis, content analysis, and conceptual synthesis to identify correlation patterns between variables. The results indicate that stringent monitoring increases evaluative pressure and cognitive load, contributing to a decline in mental well-being, whereas leadership that supports autonomy and psychological safety serves as a protective factor. This research contributes to the development of a conceptual model based on cyber-psychology that integrates technological, psychological, and leadership aspects into a single analytical framework to support more sustainable organizational practices.